Developing a secure mechanism for Bluetooth-based Wireless Personal Area Networks (WPANs) - Othman, Marini; Hassan, Wan Haslina; Hassan Abdalla Hashim, Aisha (IEEE, 2007)
This paper highlights our work in developing an enhanced security framework for Bluetooth-based wireless personal area networks (WPANs). The basic security architecture of Bluetooth, operating at the link layer, is augmented with a higher application layer security mechanism for authentication and message integrity. This is necessary since the present Bluetooth security has certain drawbacks in its implementation making it insecure. The use of digital signatures and trusted or certified public keys form the basic premise and approach in this work in providing stronger security for WPANs. Our work involves developing a prototype for Bluetooth systems using RSA and DSA encryption algorithms. An analysis was done to ascertain which of these algorithms is more suited to our proposed security framework and the results indicated that in most instances, the RS A performed better.